Determination of moment of inertia for162-168Hf and164-176Yb deformed nuclei - Okhunov.A.A,; Hasan Abu Kassim,; Usmanov .Ph .N, (Universiti Kebangsaan Malaysia, 2011)
In this paper, a method of defining the even-even deformed nuclei inertial parameters is suggested. Calculations for isotopes 162-168Hf and 164-176Yb are listed. The parameters of inertia of rotational nuclei are also defined. Dependence of the parameters of inertia on the nucleons number is shown.